Modelling Logistic Decision-Making Optimization Techniques: A Longitudinal Study of the Seaport of Aqaba - Karasneh, Abed Al-Fatah Abed Al-Rohman (International Journal of Supply Chain Management, 2020)
Through a correlative comparative analysis, the purpose of this study is to utilize LP and the data accumulated between (2009- 2017) to investigate the optimality of the current transportation strategy of actual costs to transport major Jordanian exports and imports. Study findings reveal that current exporting and importing strategies are ineffective. Results assert that decision-makers have not developed nor have taken the required action needed to resolve excessive expenditures. The current study poses some implications and recommendations as a strategic technique within decision-making paradigms to utilize effective decision making to minimize transportation costs.